2023
DOI: 10.3389/fimmu.2023.1258388
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches for FGFR-altered urothelial carcinoma: targeted therapies and immunotherapy

David J. Benjamin,
Robert Hsu

Abstract: The treatment of metastatic urothelial carcinoma has dramatically changed over the past decade with the approval of several therapies from multiple drug classes including immune checkpoint inhibitors, targeted therapies, and antibody drug conjugates. Although next generation sequencing of urothelial carcinoma has revealed multiple recurring mutations, only one targeted therapy has been developed and approved to date. Erdafitinib, a pan-fibroblast growth factor receptor (FGFR) inhibitor, has been approved for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The clinical trial NCT02792192 reported 3% complete response, 37% partial response and 39% stable disease (median progression-free survival of 5.5 months). Notably, FGFR2 and FGFR3 gene mutations are especially relevant; mutations FGFR2 N549H , FGFR3 Y373C;V555M , increase tumor immunity to FGFR-inhibitors [65,66].…”
Section: Intravesical Delivery Systemsmentioning
confidence: 99%
“…The clinical trial NCT02792192 reported 3% complete response, 37% partial response and 39% stable disease (median progression-free survival of 5.5 months). Notably, FGFR2 and FGFR3 gene mutations are especially relevant; mutations FGFR2 N549H , FGFR3 Y373C;V555M , increase tumor immunity to FGFR-inhibitors [65,66].…”
Section: Intravesical Delivery Systemsmentioning
confidence: 99%
“…A subsequent version of the device, the TAR-210, has now been developed to deliver Erdafitinib, a selective pan-FGR tyroskin kinase inhibitor that targets the FGFR3 mutation, which has been identified as an oncogenic driver in urothelial cancer [40]. An oral formula-tion of the drug has been approved for use in patients with locally advanced or metastatic urothelial cancers.…”
Section: New Developments and Future Directionsmentioning
confidence: 99%
“…Amplifications, mutations, and rearrangements of FGFRs have been frequently reported to drive tumor initiation and progression, especially in urothelial carcinoma (UC). In early-stage UC, over half of the cases show FGFR3 alterations [92], while around 20% of advanced/metastatic UC cases have FGFR3 mutations. Various FGFR kinase inhibitors have shown promise in targeting both cancer cells and the tumor microenvironment (TME).…”
Section: Fibroblast Growth Factor Receptors (Fgfrs)mentioning
confidence: 99%